The effect of Phenolic extract of the green alga Chara vulgaris on the Cysticercus of Taenia taeniaeformis - Al-Sultan, Emad Yousif; Abdullah, Basim Hashim; Al-waeli, Aqeel Abdulsahib (Iraqi Journal of Aquaculture, 2021)
The present study was made to observe the effect of phenolic extract isolated from the green alga Chara vulgaris on the larval stage (Cysticercus) of Taenia taeniaeformis in mice infected in the laboratory compared with two sets of control and Albendazole drug. It found The phenolic extract, after 3 days of treatment has more effect on the larval stage of T.taeniaeformis from Albendazole drug.The lowest average number of live larvae was 3.75 larvae at concentrations of 0.065 and 0.115 mg/kg of the phenolic extract and the highest average was5 larvae at the concentrations of 0.015 and 0.2 mg/kg of phenolic extract and Albendazole, respectively, while the lowest average number of dead larvae reached 2.5 larva by the same two concentrations.The highest average reached 6 larvae at the concentration of 0.115 mg/kg of phenolic extract, while the lowest percentage of dead larvae was 33.33% at the concentration of 0.015 and 0.2 mg/kg of phenolic extract and Albendazole, respectively.The highest percentage (61.53%) at the concentration of 0.115 mg/kg of the phenolic extract.The higher therapeutic efficiency was (63.96%) at the concentrations 0.065 and 0.115 mg/kg of the phenolicextract and the lowest the rapeutic efficiency (51.59%) was at the concentration of 0.015 and 0.2 mg/kg of the phenol and Albendazole, respectively.